Retrospective Evaluation of Death Cases Related with Suicide Occurred in Konya Between 2000 and 2005 - Demirci, Şerafettin; Günaydın, Gürsel; Doğan, Kamil Hakan (The Bulletin of Legal Medicine, 2007)
Suicide is a judicial event that is encountered frequently as a death cause among adults and adolescents and affects people of all age, race and class. The aim of this study is to determine the sociodemographic properties of death cases related with suicide in Konya and its significance from the forensic medicine point of view as well as to compare the data with literature. Of 2698 death cases within the Konya Forensic Medicine Department Directorship between 01.01.2000 and 31.12.2005, 220 (8.2%) cases of suicide were evaluated retrospectively. The manners of deaths were determined by consultation and autopsy findings. The cases were investigated according to age, gender, method of suicide, monthly and daily timeframe, psychiatric comorbidity and presence of previous suicide attack. 157 (71.4%) events out of 220 death cases related with suicide were male and 63 (29.6%) of them were female. The ages of these cases were between 10 and 94 and the average age was found as 38.7 ± 18.7 years. Deaths related with suicide occurred frequently between ages 20 and 29 with 54 (24.5%) cases. The frequency of suicide method used in descending order is as follows; hanging 105 (47.8%) cases, firearm injuries 51 (23.2%) cases (30 guns, 21 shotguns), botulism 39 (17.7 %) cases and finally jumpmg(s) from a high place 15 (6.8%) cases. Giving active and effective services to children and adolescents by psychology and guiding departments in schools, delivery of psychological support service to those who have a suicide attack history, a psychological illness such as depression and a tendency for a suicide will most likely lead to a decrease in the numbers of deaths related with suicide and in the rates ol suicide attackKey words: Suicide, forensic medicine, death.
Keywords: suicide; forensic medicine; death